2011
DOI: 10.1016/j.pbb.2010.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Sigma (σ) receptor ligand, AC927 (N-phenethylpiperidine oxalate), attenuates methamphetamine-induced hyperthermia and serotonin damage in mice

Abstract: Methamphetamine interacts with sigma (σ) receptors and AC927, a selective σ receptor ligand, protects against methamphetamine-induced dopaminergic neurotoxicity. In the present study, the effects of AC927 on methamphetamine-induced hyperthermia and striatal serotonergic neurotoxicity were evaluated. Male, Swiss Webster mice were injected (i.p.) every two hours, for a total of four times, with one of the following treatments: Saline + Saline; Saline + Methamphetamine (5 mg/kg); AC927 (5, 10, 20 mg/kg) + Methamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 55 publications
5
36
0
Order By: Relevance
“…AC927 significantly attenuated both apoptotic and necrotic cell death, which is consistent with the role of receptors in cell death mechanisms (Bowen, 2000;Marrazzo et al, 2011). Furthermore, the protective effects of AC927 in NG108-15 cells are complementary and consistent with the neuroprotection observed in earlier in vivo studies (Matsumoto et al, 2008;Seminerio et al, 2011). In tumor cells, AC927 has been shown to prevent apoptosis caused by 2 receptor agonists, underscoring an important role of receptors in cell death mechanisms (Marrazzo et al, 2011).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…AC927 significantly attenuated both apoptotic and necrotic cell death, which is consistent with the role of receptors in cell death mechanisms (Bowen, 2000;Marrazzo et al, 2011). Furthermore, the protective effects of AC927 in NG108-15 cells are complementary and consistent with the neuroprotection observed in earlier in vivo studies (Matsumoto et al, 2008;Seminerio et al, 2011). In tumor cells, AC927 has been shown to prevent apoptosis caused by 2 receptor agonists, underscoring an important role of receptors in cell death mechanisms (Marrazzo et al, 2011).…”
Section: Discussionsupporting
confidence: 81%
“…Previous in vivo studies showed that pretreatment with N-phenethylpiperidine oxalate (AC927), a receptor ligand, attenuates the neurotoxic effects of METH in male SwissWebster mice (Matsumoto et al, 2008;Seminerio et al, 2011). The ability of AC927 to mitigate neurotoxic cascades is consistent with the location of receptors in various subcellular organelles, such as ER, mitochondria, lysosomes, cell membranes, and nuclei (McCann et al, 1994;Zeng et al, 2007), as well as the functional roles of receptors in cells, as described above.…”
Section: Introductionmentioning
confidence: 54%
“…Moreover, it produces similar protective effects as other more selective sigma ligands such as AC927 and CM156 in mitigating a number of earlier studied METH-induced endpoints (Kaushal et al 2011b; Seminerio et al 2011). Additionally, SN79 represents a potential drug development candidate aimed at treating the negative side effects of METH abuse such as neurotoxicity, as it has not only desirable pharmacologic effects, but also desirable pharmacokinetic parameters as well (Kaushal et al 2011a).…”
Section: Discussionmentioning
confidence: 69%
“…SN79 has been shown in earlier studies to attenuate a number of METH-induced effects including microglial activation (Robson et al 2013) and other classical striatal dopaminergic and serotonergic deficits which are similarly mitigated by other sigma receptor antagonists (Kaushal et al 2011b; Seminerio et al 2012a; Seminerio et al 2011). Secondly, we wanted to determine if sigma receptor modulation results in a blockade of OSMRβ/gp130-induced STAT3 phosphorylation which has been implicated in the activation of astrocytes following CNS insults.…”
Section: Introductionmentioning
confidence: 99%
“…Hypophysectomy, Drug-Induced Neuroplasticity thyroparathyroidectomy, as well as treatment with high doses of haloperidol or diazepam that reduce body temperature during amphetamine treatments, also reduce the observed toxicity Sprague et al, 2003). A large number of neurotransmitter systems appears to be involved in producing the hyperthermic effect, because blockade of receptors, including the NMDAR; D 1 R, D 2 R, and D 3 R; a1-adrenoreceptors; 5-HT 2 receptors; as well as the s and OX 1 receptors, all prevent or reduce METH-induced hyperthermia while protecting against METH toxicity (Sonsalla et al, 1991;Farfel et al, 1992;Doyle and Yamamoto, 2010;Seminerio et al, 2011Seminerio et al, , 2012Rusyniak et al, 2012;Ares-Santos et al, 2012;Kikuchi-Utsumi et al, 2013;Robson et al, 2013a;Sabol et al, 2013;Baladi et al, 2014).…”
Section: Action Of Substituted Amphetamines and Cathinonesmentioning
confidence: 99%